2015
DOI: 10.1017/s1751731114003309
|View full text |Cite
|
Sign up to set email alerts
|

The use of novel phenotyping methods for validation of equine conformation scoring results

Abstract: In this experiment, which is based on a cohort of 44 Lipizzan mares from the Austrian state stud farm of Piber, we present new statistical techniques for the analysis of shape and equine conformation using image data. In addition, we examined which strategies and procedures of image processing techniques led to a successful interpretation of the traits implemented in horse breeding programs. A total of 246 two-dimensional anatomical and somatometric landmarks were digitized from standardized photographs, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…; Druml et al . ). Furthermore, the number of horses ( n = 1077) is still quite limited to typical GWAS for complex traits in humans or even cattle.…”
Section: Resultsmentioning
confidence: 97%
“…; Druml et al . ). Furthermore, the number of horses ( n = 1077) is still quite limited to typical GWAS for complex traits in humans or even cattle.…”
Section: Resultsmentioning
confidence: 97%
“…Previous analyses of shape variation and conformation judging preferences in the Lipizzan population of Piber (Druml et al, 2015(Druml et al, , 2016 demonstrated that the classical Iberian or baroque Lipizzan type represents the ideal breeding goal. The advantage of this image-based morphometric approach over conventional linear measuring methods is that the retrieved model horses can be easily understood and can be used for the adjustment of conformation scoring protocols and/or breeding goals in the context of breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…For the same set of animals, which represents the actual state-owned Austrian Lipizzan breeding population, we collected standardized digital photographs following the protocol of Druml et al (2015Druml et al ( , 2016) (see Fig. S1 in the Supplement).…”
Section: Pedigree Analyses and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum assessment of young horses seems particularly important because improvements in the breeding efficiency of cold-blooded horses are seen in shortening the generation interval (Mantovani et al 2013), especially as the expression of some traits in cold-blooded horses changes with age, which means that it is more heritable in young horses (Mantovani et al 2010;Suontama et al 2011). The type is a trait characterized by greater scoring conventionality both in our study and in other studies (Druml et al 2015). The scores and correlations obtained are largely dependent on within-breed variation in the studied traits (Komosa et al 2013), which was rather limited in the present study.…”
Section: Discussionmentioning
confidence: 48%